Quantifying Transaction Costs in Online/Off-line Grocery Channel Choice - Chintagunta, Pradeep K.; Chu, Junhong; Cebollada, Javier (Marketing Science, 2012)
Households incur transaction costs when choosing among off-line stores for grocery purchases. They may incur additional transaction costs when buying groceries online versus off-line. We integrate the various transaction costs into a channel choice framework and empirically quantify the relative transaction costs when households choose between the online and off-line channels of the same grocery chain. The key challenges in quantifying these costs are (i) the complexity of channel choice decision and (ii) that several of the costs depend on the items a household expects to buy in the store, and unobserved factors that influence channel choice also likely influence the items purchased. We use the unique features of our empirical context to address the first issue and the plausibly exogenous approach in a hierarchical Bayesian framework to account for the endogeneity of the channel choice drivers. We find that transaction costs for grocery shopping can be sizable and play an important role in the choice between online and off-line channels. We provide monetary metrics for several types of transaction costs, such as travel time and transportation costs, in-store shopping time, item-picking costs, basket-carrying costs, quality inspection costs, and inconvenience costs. We find considerable household heterogeneity in these costs and characterize their distributions. We discuss the implications of our findings for the retailer's channel strategy.